2012
DOI: 10.1021/ie202193m
|View full text |Cite
|
Sign up to set email alerts
|

Reboiler Separation Efficiencies for Binary Systems

Abstract: Reboilers are essential for the proper work of distillation and stripping columns. Hereby the intensity of axial mixing along the reboiler (Peclet number) is used for the reboiler separation efficiency modeling and estimation for binary systems. Two fully worked examples show that the separation (Murphree) efficiency varies significantly depending on the adopted reboiler flow model. Murphree efficiency ranges between 1.40 and 0.663 in example 1, and between 1.962 and 1 in example 2. The general conclusion is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The simulation model always assumed that the reboiler would act as a (phase-)equilibrium stage and was thus not able to predict the performed experiments. Keskinen et al [63] and Jaćimović et al [64] found that a reboiler exhibits a non-ideal behavior depending on (1) the type of reboiler, (2) the vaporization fraction and (3) the wideness of the boiling points of the components present. They found that naturally circulating reboilers do not act as (phase-)equilibrium stages.…”
Section: Non-ideality Of the Naturally Circulating Reboilermentioning
confidence: 99%
“…The simulation model always assumed that the reboiler would act as a (phase-)equilibrium stage and was thus not able to predict the performed experiments. Keskinen et al [63] and Jaćimović et al [64] found that a reboiler exhibits a non-ideal behavior depending on (1) the type of reboiler, (2) the vaporization fraction and (3) the wideness of the boiling points of the components present. They found that naturally circulating reboilers do not act as (phase-)equilibrium stages.…”
Section: Non-ideality Of the Naturally Circulating Reboilermentioning
confidence: 99%